Narrative Review: Lean Management dalam Pengelolaan Perbekalan Farmasi - Abdul Hadi; Diesty Anita Nugraheni (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
Effective administration of pharmaceutical supplies is absolutely essential for maintaining the quality of care provided by healthcare facilities. Deficiencies in healthcare service quality are often rooted in management practices that are both ineffective and suboptimal within the supply chain. To address these inefficiencies, Lean Management presents a viable framework for adoption within the healthcare environment. This paper summarizes existing literature through a narrative review specifically focusing on how lean principles are applied to the management of pharmacy stock. The methodology involved a systematic search using Boolean logic across major databases, including PubMed, ScienceDirect, and Google Scholar. From a starting pool of 96 articles, nine were ultimately selected based on the defined inclusion criteria. The compiled research findings consistently and unanimously suggest that incorporating lean methodologies offers substantial advantages. These advantages are realized primarily through the ability to minimize operational waste (such as excess inventory, unnecessary movement, or excessive waiting times) and simultaneously boost the overall efficiency of the pharmacy supply chain. Implementing Lean Management is therefore an effective strategy for optimizing logistics and improving service quality in pharmaceutical provision.